Oceanlens: Augmented Reality Experience Of Pulau Redang Marine Life - Muhammad Fitri , Muhammad Beyazid Yeldrim; Mohd Salimi , Nor Hidayu (Journal of Computing Technologies and Creative Content, 2025)
Pulau Redang, a well-known marine tourism spot in Malaysia, is facing serious environmental problems such as coral reef damage, pollution, and loss of marine life due to rising tourist activities. Traditional ways of teaching conservation often do not catch the attention of tourists, so new methods are needed to spread awareness and encourage responsible behavior. This study introduces OceanLens, an Augmented Reality (AR) mobile application designed to help users learn about marine conservation in a fun and interactive way. The app lets users explore digital 3D models of marine life, coral reefs, and pollution effects, making it easier to understand the impact of human actions on the ocean. Using the ADDIE model for development and a mix of surveys and usability testing, the study evaluated how well OceanLens helps users learn, stay engaged, and change behavior. Results show that AR helps users better understand and care about marine ecosystems, leading to more environmentally friendly actions. However, there were some challenges, such as poor internet connection at Pulau Redang, which can affect the AR experience. Also, some users had trouble using the app on certain devices, showing the need for better optimization. This study suggests that AR can be a powerful tool in conservation education. Other mobile apps, like Seek by iNaturalist or WWF Free Rivers, can also be useful for environmental learning in Malaysia. Future improvements could include adding more languages, AI features, and using AR in other ecotourism locations. By combining technology and education, OceanLens aims to support sustainable tourism and protect Malaysia’s marine heritage for future generations.